Retrospective conversion of card catalogs: the experience of Russian libraries - A. A. Stukalova (Библиосфера, 2012)
The activity of the Russian libraries in the field of retrospective conversion of card catalogue is analyzed. The main ways of retrospective conversion are shown. Considered are the results of this activity.